NIKAH SIRRI DAN IMPLIKASINYA TERHADAP ANAK YANG DILAHIRKAN: (Menurut Madzhab Syafi’i dan Undang-undang No.1 Tahun 1974 tentang Perkawinan) - Hakim, Luthfi; Faruq, Ahmad (Irtifaq, 2021)
This article is aimed at discussing Sirri marriage and its implications for children born according to the Madzab Syafi'i and Law No.1 of 1974 on Marriage. By using the library research approach, the research examines the references of these two sources to, describe the implications of Sirri marriage to the child born. The result shows, first the marriage is permitted and legal according to the Madzab Syafi'i since the requirement of the marriage can be fulfilled.  Second, Law No. 1 of 1974 on Marriages that have been indirectly confirmed with KHI, prohibits marriages performed in Sirri, because it does not comply with the terms and conditions of registration, so that the Sirri marriage is considered invalid and has no legal force; third, the status of the child born is considered an illegitimate child. Children born as a result of Sirri's marriage, despite fulfilling the pillars and conditions of marriage, but not recorded legally, are considered invalid children. implication, the child has no civil relationship with his father, but only has a civil relationship with his mother and his mother's family, the child has no right inheritance from his father. Keywords: Sirri Marriage, Legal Implications